Penulisan Sejarah Desa: Sebuah Model Pembelajaran untuk Tugas Akhir Mahasiswa - Mochammad Nginwanun Likullil Mahamid; Dina Ayu Ardhana; Ilham Nur Rochmad; Queen Tamalla Hasan; Hanip Hidayatulloh (Yayasan Zia Salsabila, 2024)
Writing a final assignment or thesis is a requirement for graduation from an undergraduate (S1) program, enabling students to develop skills in exploring ideas, identifying problems, analyzing data, and presenting findings in an academic format. Emphasizing novelty is crucial to producing high-quality theses that contribute to their field of study. However, recent final assignments by students of the Islamic Civilization History Program at UIN Sunan Ampel Surabaya have largely focused on topics such as mosques, Islamic boarding schools, traditions, and religious figures, while other potential topics, like Village History, remain underexplored despite their capacity to achieve higher academic value. This aligns with the Ministry of Home Affairs Regulation (Permendagri) No. 50 of 2021, which supports the